2010
DOI: 10.1007/s12029-010-9228-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Diverse Populations, British Columbia, Canada, and Ardabil, Iran, Indicates Several Variables Associated with Gastric and Esophageal Cancer Survival

Abstract: BackgroundGeographic variation and temporal trends in the epidemiology of esophageal and gastric cancers vary according to both tumor morphology and organ subsite. This study compares 1-year survival of gastric and esophageal cancers between two distinct populations: British Columbia (BC), Canada, and Ardabil, Iran.MethodsData for invasive primary esophageal and gastric cancer patients were obtained from the population-based cancer registries for BC and Ardabil. The relative survival rate was calculated using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In addition, for studies of esophageal cancer, the location of tumors also showed differences in survival. Tumors in the middle 1/3 of the esophagus show worse survival in Turkey and Ardabil (Iran) [ 30 , 31 ], but tumors in the lower 1/3 of the esophagus are reported to have worse survival in BC and the United States[ 21 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, for studies of esophageal cancer, the location of tumors also showed differences in survival. Tumors in the middle 1/3 of the esophagus show worse survival in Turkey and Ardabil (Iran) [ 30 , 31 ], but tumors in the lower 1/3 of the esophagus are reported to have worse survival in BC and the United States[ 21 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite advances in conventional therapies, the survival rate of patients with GC up to 5 years is poor (o30%), thus GC accounts for the fourth most commonly diagnosed cancer and the second most common cause of cancer-related death worldwide. 3 The etiology of GC is multifactorial including environmental, genetic and infectious factors. 2,[4][5][6] Multiple evidence demonstrated the important role of Helicobacter pylori (H. pylori) infection in the development of GC.…”
Section: Introductionmentioning
confidence: 99%
“…In addition for TP53 gene, we have observed in the results of our meta-analysis that it is associated with BC, UBC, CRC, EC and LC [80-87,96-100,104-108,111-113,149]. We have observed also that TP53 gene might be associated with OC [88,148], too.…”
Section: Resultsmentioning
confidence: 71%